Chaos Based Image Encryption - Suresh. G. B; V. Mathivanan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
New method of secure image encryption and decryption scheme based on the chaos is proposed. There are two steps are followed after the preprocessing step in the proposed system namely, Encryption and Decryption. In preprocessing, images are denoised using median filter. Then the original input images will be encrypted by using the chaos mapping algorithm. At last the original images are retrieved back from the encrypted image by using the key that is specified during the encryption process for the decryption of the original images. Then the histogram mapping is done for the encrypted and the decrypted images. The proposed system is tested on well-known images like Lena, Mandrill, Clown and Barbara. The experimental results have demonstrated that the introduced image encryption scheme can achieve high security for practical image encryption.